Including the voice of the patient in healthcare: new models for health and design - Harvey, Gillian (InfoDesign, 2026)
This paper examines how design methods – specifically information design and participatory design – can strengthen the voice of the patient within healthcare systems, particularly for equity-seeking populations. Drawing on the Cascade of Care Framework used in healthcare as a conceptual model, the paper explores opportunities for designers to intervene across stages of awareness, engagement, retention, treatment, and outcomes. Three case studies from the Design Health Research Innovation Lab at the University of Alberta illustrate how co-design, narrative methods, and information design tools can enhance health system engagement, reduce stigma, and improve health literacy. These cases include: Addictions Don’t Discriminate, a public exhibition co-created with people who experience addiction; Supporting Healthy Partnerships with People Who Use Drugs, a toolkit and learning intervention supporting equitable collaboration; and a digital and print opioid education toolkit developed with communities and clinicians. The paper, originally presented as a keynote, discusses the idea that design can make patient involvement more meaningful, sustainable, and impactful, particularly when lived experience is treated as expertise and when information is made clear, accessible, and actionable. The paper concludes by identifying future directions for design research in health, emphasizing the need for equity, digital accessibility, and long-term co-design partnerships.